DAMPAK PENURUNAN RUANG TERBUKA HIJAU TERHADAP EKONOMI, SOSIAL DAN LINGKUNGAN DAERAH ( STUDI KASUS EKSPANSI PARIWISATA DIKOTA BATU ) - Lestari Harahap; Pratiwi Dwi Karjati (widya balina, 2025)
Batu City, as a major tourist destination, has experienced rapid growth in tourism infrastructure development, leading to the conversion of agricultural land and green open spaces into commercial areas. Using a case study methodology and a qualitative approach, this study gathers data in many sub-districts through documentation, in-depth interviews, and observation, including Sidomulyo, Songgokerto, and Oro-Oro Ombo. The findings indicate that the decline in Green Open Space (GOS) has negatively impacted environmental quality (such as rising temperatures and increased flood risk), disrupted the livelihoods of agricultural communities, and caused economic disparities due to the dominance of the tourism service sector. While tourism contributes to regional income, without sustainable environmental management, the long-term economic potential may decline. Therefore, a tourism development strategy that balances economic growth with environmental preservation is essential.